Online Resilience Support Groups During the COVID-19 Pandemic: The Philippine Experience - Hechanova, Ma. Regina (Archīum Ateneo, 2021)
The purpose of this paper is to examine the outcomes of an online resilience support group during the COVID-19 pandemic in the Philippines. Specifically; it described the extent to which the program improved adaptive coping; non-reactivity; resilience and well-being and decreased stress; depression and anxiety symptoms of participants. This study used a pretest–posttest design with 53 participants. A majority of participants were female (74%) who participated in the program for 6–8 weeks. Scales measuring adaptive coping; non-reactivity; resilience; well-being; stress; depression and anxiety were administered before and after the completion of the modules. Results revealed significant improvements in adaptive coping particularly seeking emotional and instrumental support; active coping; and religious coping. The results also showed significant improvements in nonreactivity; psychological well-being and resilience and decrease in depression symptoms. Effect size estimates indicate medium effect sizes for well-being and nonreactivity with the other outcomes having small effect sizes. This paper examines the feasibility of an online structured peer support group that focuses on building resilience skills. It fills a gap in the literature on online peer support groups that may be most relevant for low-income countries with a dearth of mental health specialists.